2020
DOI: 10.3904/kjim.2017.415
|View full text |Cite
|
Sign up to set email alerts
|

A prospective survey of the persistence of warfarin or NOAC in nonvalvular atrial fibrillation: a COmparison study of Drugs for symptom control and complication prEvention of Atrial Fibrillation (CODE-AF)

Abstract: Background/Aims: Efforts to reduce stroke in patients with atrial fibrillation (AF) have focused on increasing physician adherence to oral anticoagulant (OAC) guidelines; however, the high early discontinuation rate of vitamin K antagonists (VKAs) is a limitation. Although non-VKA OACs (NOACs) are more convenient to administer than warfarin, their lack of monitoring may predispose patients to nonpersistence. We compared the persistence of NOAC and VKA treatment for AF in real-world practice. Methods: In a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
0
19
1
1
Order By: Relevance
“…Our previous study showed that OAC was used in 82.7% of patients, and NOAC in more than two-third of OAC prescribed patients in this registry 17 . Moreover, persistence to OAC declined for 6 months only to 95.5% for NOAC 37 . Therefore, high OAC rate with high NOAC usage, and high persistent rate might be related with low stroke rate in this study.…”
Section: Study Limitationsmentioning
confidence: 94%
“…Our previous study showed that OAC was used in 82.7% of patients, and NOAC in more than two-third of OAC prescribed patients in this registry 17 . Moreover, persistence to OAC declined for 6 months only to 95.5% for NOAC 37 . Therefore, high OAC rate with high NOAC usage, and high persistent rate might be related with low stroke rate in this study.…”
Section: Study Limitationsmentioning
confidence: 94%
“…Nevertheless, the therapeutic range for all VKA drugs is usually unsatisfactory; as a consequence, thromboembolic and hemorrhagic events are more frequent in patients treated with VKAs than DOACs [ 112 , 114 , 115 , 116 , 117 ]. Lastly, although treatment adherence was comparable between DOACs and VKAs, treatment satisfaction and persistence are significantly lower with VKAs than DOACs; CKD and history of bleeding represent some of the main factors associated with absence and/or non-adherence to anticoagulant therapy in everyday practice [ 97 , 118 , 119 , 120 ].…”
Section: Non-anticoagulative Approachesmentioning
confidence: 99%
“…3 Non-vitamin K oral anticoagulant use in clinical practice is increasingly becoming the standard of care. Several registries [4][5][6] and retrospective analyses 7,8 have assessed outcomes of three (apixaban, dabigatran, and rivaroxaban) of the four available NOACs, but routine clinical data on edoxaban, the fourth NOAC that entered the clinical arena, are scarce. Regulators such as the European Medicines Agency have regularly requested for data on the safety of recently approved therapies in routine clinical care as part of the postapproval safety plan of these recently approved medications.…”
Section: Introductionmentioning
confidence: 99%